ECONOMIC SECURITY OF THE EUROPEAN UNION IN THE LIGHT OF THE DIGITAL BUSINESS MODELS APPLIED BY THE MULTI-NATIONAL ENTERPRISES - TIM Artur (2018)
The issue of economic security and fiscal matters are closely connected to each other, especially taking into account the massive non-taxation of the digital business models, which can be observed in the present economic reality. The non-effective taxation of the digital business models together with fiscal losses caused by this phenomenon are nowadays as high on the international, political agenda as e.g. climate change. European Union has been even called as “vulnerable” to tax planning activities, made by digital enterprises. The essence of the discussed in the Article issue is that the fundamental rules of the international tax law were created in the late 19th century and well-established during the 20th century – in the reality, in which the digital business models could not have been even predicted. As a result of application of these outdated rules, the income generated in the source state cannot be there taxed. Furthermore, this activity does not constitute a breach of tax law and cannot be perceived as tax evasion or tax avoidance. The European Commission initiated the proceedings against Ireland for illegal state aid, received by Apple in the amount of 13 billion EUR (taxes unpaid in relation to transfer pricing rules, unlawfully approved by the Irish tax authorities). Almost at the same time, as a result of D. Trump’s tax reform, Apple agreed to pay voluntary in the U.S. 38 billion USD in taxes, invest350 billion USD and create there over 20.000 jobs. In Spring 2018, as a result of the demand requested by the Member States, the European Commission presented a project to overcome non-effective taxation of the digital business models in the European Union. However, the adoption of the project is unlikely to happen– for the reason of the requirement to reach unanimity between states (until now some states expressed objections or even rejected the project), as well as grounding the long-term solution on the idea, which has already been rejected by the Member States in 2011.In the article the Author describes the reasons for a lack of effective taxation of the digital business models in the source state, outlines the essence of the economic security and influence on it made by the tax planning schemes, applied by digital enterprises, as well as drafts the particular position of the Multi-National Enterprises in the post-globalised world. In the article are also presented means of reaction, coined on the international and European level to overcome that challenge, posed before the modern societies. The Author stresses also that having regard these particularities of the income taxation, in the international tax law doctrine more and more often the idea of abolishing income taxes is taken into consideration, especially in relation to the CIT (corporate income tax).